1983
DOI: 10.1113/jphysiol.1983.sp014838
|View full text |Cite
|
Sign up to set email alerts
|

Directional tuning interactions between moving oriented and textured stimuli in complex cells of feline striate cortex.

Abstract: SUMMARY1. In sixty-five complex cells recorded from striate cortex of lightly anaesthetized, paralysed cats we investigated directional selectivity for motion of oriented and textured stimuli, both alone and when-moving simultaneously in the same direction and at the same velocity. Monocular comparisons were made over a range of velocities for the dominant eye in all cells, and for the other eye in fourteen instances.2. For oriented stimuli, response magnitude varied with velocity, but preferred directions(s) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 27 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…They proposed an explanation that at spatial frequencies higher than optimum a grating oriented off-axis has a projection on the original preferred-null axis at a lower equivalent spatial frequency, closer to the optimum, and thus evokes a stronger response than the same grating oriented on-axis. A similar splitting of direction tuning curves for textures at high speeds has been observed by Hammond and Smith (1983) in their study on cat complex cells, again only in a proportion of cells, but an analogous explanation, although considered, was rejected in that study. Grzywacz and Amthor (2007) have also found the bandwidths of speed tuning of On-Off DS RGCs for a grating and for a spot to be slightly different, the latter being somewhat broader.…”
Section: Other Stimulus Dimensions and Typesmentioning
confidence: 51%
See 1 more Smart Citation
“…They proposed an explanation that at spatial frequencies higher than optimum a grating oriented off-axis has a projection on the original preferred-null axis at a lower equivalent spatial frequency, closer to the optimum, and thus evokes a stronger response than the same grating oriented on-axis. A similar splitting of direction tuning curves for textures at high speeds has been observed by Hammond and Smith (1983) in their study on cat complex cells, again only in a proportion of cells, but an analogous explanation, although considered, was rejected in that study. Grzywacz and Amthor (2007) have also found the bandwidths of speed tuning of On-Off DS RGCs for a grating and for a spot to be slightly different, the latter being somewhat broader.…”
Section: Other Stimulus Dimensions and Typesmentioning
confidence: 51%
“…However, some other evidence suggests that it may not be so straightforward. Hammond and Smith (1983), for example, have shown in complex cells of cat striate cortex that direction tuning curves may be subject to change depending on the exact stimulus configuration. They have shown that the preferred direction for a bar and for a texture in the same cell may be different, the direction tuning curves for these two stimuli may have different bandwidths, and the shape of the direction tuning curve for texture alone is affected by speed.…”
Section: Other Stimulus Dimensions and Typesmentioning
confidence: 98%
“…Bimodal responses were normally generated by higher velocities of the rotating noise field, while unimodal responses were obtained with lower velocities (Hammond and Smith, 1983). In many cases, the response types (bi-or unimodal) could be changed with the stimulus velocity.…”
Section: Comparison Of the S Componentsmentioning
confidence: 99%
“…Flashing bars or moving noise field stimuli contain only the orientational or the directional component respectively, and have therefore been used for a comparison of the tuning strengths with those obtained by a moving bar (Henry et al, 1973(Henry et al, , 1974bHammond, 1978;Hammond and Reck, 1980;Duysens and Orban, 1981;Emerson and Coleman, 1981;Hammond and Smith, 1983). In previous studies the quantification of the tuning parameters has normally been performed by heuristic measures, such as the direction index or the half-widthat-half-height orientation tuning parameter (Orban, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…3 and 4 in Crook 1990;Fig. 5 in Hammond and Smith 1983), although directional tuning curves become broad and bi-lobed around peaks at high-velocity dot or pattern stimuli (Crook 1990;Hammond and Reck 1980;Hammond and Smith 1983;Skottun et al 1988).…”
Section: Predicting Fmri Adaptation Curves By the Two-stage Modelmentioning
confidence: 99%